Effects of SiO2, Al2O3 and Fe2O3 on leachability of Zn, Cu and Cr in ceramics incorporated with electroplating sludge. Issue 4 (August 2017) - Li, Meijuan; Su, Peng; Guo, Yina; Zhang, Wenyi; Mao, Linqiang
Highlights: Effects of SiO2, Al2 O3 and Fe2 O3 on fate of Zn, Cu and Cr were examined. Zn preferably form ZnCr2 O4 in comparison to ZnAl2 O4 and ZnFe2 O4 . Cu can only be transformed into CuAl2 O4 and CuFe2 O4 . SiO2 inhibit Cr(III) oxidation comparing with Al2 O3 and Fe2 O3 . Abstract: Large amounts of electroplating sludge generated in electroplating industry require recycling or alternative recovery solutions to minimize environmental impact caused by the waste. The use of electroplating sludge as raw materials in the production of building materials is a feasible alternative to valorize this waste. In this study, the effects of SiO2, Al2 O3 and Fe2 O3 on the leachability of heavy metals (i.e. Zn, Cu and Cr(III)) during firing ceramics with the addition of electroplating sludge were examined. The results showed that Zn preferably combined with Cr(III) to form ZnCr2 O4 in comparison to the formation of ZnAl2 O4 and ZnFe2 O4, and Zn could also be incorporated into Zn2 SiO4 structure. However, Zn spinel structure have better resistance against acid attack comparing with Zn2 SiO4 . Cu can only be transformed into spinel phases of CuAl2 O4 and CuFe2 O4 . SiO2, Al2 O3 and Fe2 O3 make less contributions to the immobilization of Cr(III). The presence of CaO severely impacted the formation of spinel phases, especially for Cr spinel. Moreover, Cr(III) would be oxidized into Cr(VI) due to the presence of CaO. It appears that the presence of SiO2 may inhibit the oxidation of Cr(III) comparing with Al2 O3 and Fe2 O3, which can be attributed to the interaction of CaO with SiO2 decreasing the amount of CaO. This study can provide a basic understanding for the leachability of Zn, Cu and Cr during the use of solid waste containing heavy metals in the production of clay bricks or ceramics.